Tissue Electrical Property Mapping From Zero Echo-Time Magnetic Resonance Imaging - Lee, Seung-Kyun; Bulumulla, Selaka; Wiesinger, Florian; Sacolick, Laura; Sun, Wei; Hancu, Ileana (IEEE transactions on medical imaging, 2015)
The capability of magnetic resonance imaging (MRI) to produce spatially resolved estimation of tissue electrical properties (EPs) in vivo has been a subject of much recent interest. In this work we introduce a method to map tissue EPs from low-flip-angle, zero-echo-time (ZTE) imaging. It is based on a new theoretical formalism that allows calculation of EPs from the product of transmit and receive radio-frequency (RF) field maps. Compared to conventional methods requiring separation of the transmit RF field (B 1 + ) from acquired MR images, the proposed method has such advantages as: 1) reduced theoretical error, 2) higher acquisition speed, and 3) flexibility in choice of different transmit and receive RF coils. The method is demonstrated in electrical conductivity and relative permittivity mapping in a salt water phantom, as well as in vivo measurement of brain conductivity in healthy volunteers. The phantom results show the validity and scan-time efficiency of the proposed method applied to a piece-wise homogeneous object. Quality of in vivo EP results was limited by reconstruction errors near tissue boundaries, which highlights need for image segmentation in EP mapping in a heterogeneous medium. Our results show the feasibility of rapid EP mapping from MRI without B 1 + mapping.